The Meanng in life And Depression Level Among Student - Happy Cahaya Mulya; Tri Kurniati Ambarini (Universitas Katolik Soegijapranata, 2019)
The aim of this study is to understand the relationship between meaning in life and depression levels of university students. Additionally, this study also aims to understand the relationship between the two aspects of meaning in life with depression levels. This study was done on 254 students using LRI-R to measure meaning in life and BDI-II Indo Version to measure level of depression. Data analysis technique used in this study is kendall tau_b. The result of this study shows that meaning in life has a negative relationship with level of depression on university students. Apart from that, this study also shows that both aspects of meaning in life, framework and fulfillment, have negative relationships with depression levels.